Durable Material Deposition via PTA upon Al-alloys - Caisova, Klara; Lattner, Michal; Cais, Jaromir (Manufacturing Technology Journal, 2022)
This study focuses on surface treatment of aluminium alloys by High Speed Steel (HSS30) via Plas-ma Transferred Arc. The main motivation of this research has been an assignment of local company in order to prolong the lifetime of a tire press molds, especially the interface of its segments. These segmented molds are made from aluminium alloy and their interface is exposed to multiple percus-sions, which leads to cracks. Therefore, PTA surfacing is considered as a suitable surface treatment for hardening its interface, yet benefit from lightweight of aluminium matrix. For purposes of this research AlSi9CuNiMn alloy was used as a matrix metal. Permeation in the contact zone was exam-ined via confocal and scanning electron microscope. Hardness of affected matrix area was measured by using Vickers Hardness Tester.
Keywords: PTA; Aluminium alloys; HSS30; Inconel 625; surfacing